The Process of Adjusting the Library Services in the Era of the COVID-19 Pandemic - Kadek Aryana Dwi Putra (Record and Library Journal, 2022)
Background of the study: The spread of COVID-19 has an impact on libraries so that services are adjusted. Purposes: This paper aims to share library service activities at the Faculty of Social and Political Sciences, Faculty of Psychology, Faculty of Biology and Faculty of Agriculture during the COVID-19 pandemic. This paper describes the state of the library since its closure in March 2020. In addition, this paper provides details on how libraries adapt to online services. Method: This paper describes the various library services at Gadjah Mada University at the Faculty of Social and Political Sciences, Faculty of Psychology, Faculty of Biology and Faculties Agriculture during the COVID-19 pandemic. This research uses a qualitative approach with the type of case study research. Data collection was carried out through interviews with 8 librarians and from web pages and social media from four libraries. Findings: Four faculty libraries at UGM have undergone online service transformation and implemented the COVID-19 health protocol. Libraries in the faculty of Political Science and Faculty of Psychology serve online. while libraries in the faculty of biology and faculty of agriculture have physically opened services Conclusion: Libraries have undergone a transformation during the COVID-19 pandemic by relying on online services and implementing health protocol.